Dificultades de la adopción de niños en Colombia a partir de la jurisprudencia de la Corte Constitucional entre 2011 y 2016. (2018)
This article aims to identify the administrative and judicial difficulties in the adoption process in Colombia, from the analysis of the Constitutional Court’s judgments during the years 2011 to 2016. Taking as a basis the socio-legal type research and using an analytical descriptive method based on the study of judgments, defined from questions oriented to the difficulties in the adoption process. This research identified the adoption as a mechanism oriented towards satisfying the best interests of children when the family does not guarantee the conditions for the realization and exercise of their rights. Finally, it showed that there is still a lack of precision and effectiveness in applying the regulations and principles set forth in the Convention on the Rights of the Child